The role of hijab trends in shaping Islamic character at the Institut Syekh Abdul Halim Hasan Binjai - Inggit Hertika; Arie Dwi Ningsih (EDUCTUM: Journal Research, 2026)
The development of hijab use in Indonesia has shifted its meaning from a religious obligation to a lifestyle and fashion trend, particularly among female students. This phenomenon has given rise to various perceptions regarding the role of the hijab in shaping Islamic character. This study aims to determine the role of hijab trends in shaping the Islamic character of female students at the Syekh Abdul Halim Hasan Binjai Institute. This study used a qualitative approach with a case study design. The research subjects consisted of five ninth-semester female students of the Islamic Religious Education Study Program selected through purposive sampling. Data collection techniques were conducted through observation and in-depth interviews, while data analysis used thematic analysis. The results of the study indicate that hijab trends play a role in shaping female students' identity, self-confidence, and self-awareness as Muslim women. However, the formation of Islamic character does not occur automatically through hijab use, but rather depends heavily on the understanding, awareness, and practice of Islamic values ??in everyday life. Therefore, it is recommended that female students not only follow hijab trends as a fashion symbol, but also understand their religious meaning as an effort to develop a complete Islamic character.